TRANSFIGURATION CATHEDRAL IN ODESA: THE THEMES AND THE STYLISTICS - Тарасенко, А. А.; Акрідіна, Г. В. (Art and Design, 2020)
The purpose is to study the themes and the stylistics of the upper and lower churches’ iconostases of the Transfiguration Cathedral in Odessa. The comparative method was used in order to study the topic and identify the artistic and stylistic features of Odessa Cathedral iconostases. It allows comparing the objects of study with analogues from the world art. Iconological, iconographic methods and figurative-stylistic analysis were also applied. The iconostases of the Transfiguration Cathedral upper and lower churches in Odessa are organically inscribed in the architectural environment, thanks to which the synthesis of arts is reached. Classical architecture and the original spatial architectonics of the upper temple altar barrier determined the theme and the style of the icon-painting. It was found out that the decoration and the icons in the Transfiguration Cathedral upper and lower churches’ iconostases combine the multi-temporal traditions of Christian art. The upper church central iconostasis reflects the influence of Renaissance architecture and art. The icon painting characteristic feature is a combination of the European art heritage, specifically Italian and Northern Renaissance, classicism, baroque and academicism of the XIX century. A three-dimensional style of painting based on the Western European tradition is observed. The decoration of the lower temple altar barrier contains architectural elements of Byzantium, Ancient Rus and baroque. The icon painting was created in the canonical Byzantine style of the Paleologue Renaissance period. By studying the features of the Transfiguration Cathedral iconostases, the main trends in church art of the second half of the XX–XXI centuries were identified: the application and combination of the renaissance-academic and the Byzantine-Ancient Rus styles. A detailed study of Odessa Cathedral iconostases was conducted for the first time. The features of the icon-painting themes and stylistics in the connection with the architectonics of the iconostases and the temple’s architecture were revealed. Practical significance is due to the possibility of using research materials in monographs on art history of Odessa, in the preparation of textbooks and methodological instructions with an in-depth study of icon-painting, monumental and decorative art, in the working-out of lectures’ and practical classes’ texts.